Parenting very preterm infants and stress in Neonatal Intensive Care Units - Baía, I. (2017)
Background: Assessing parental stress during infants' hospitalization in Neonatal Intensive Care Units (NICU) is essential to identify parents at risk for immediate and extended physical and emotional burden. Aims: To identify sources of stress in mothers and fathers of very preterm infants hospitalized in NICU, and their association with sociodemographic, obstetric and infants' characteristics. Study design: Observational and cross-sectional study conducted between July 2013 and June 2014. Subjects: Parents of very preterm infants hospitalized in all level III NICU in the Northern Health Region of Portugal were consecutively and systematically invited to participate in this study, being included 120 mothers and 91 fathers (participation rate: 98.6%). Outcome measures: The Portuguese version of the Parental Stressor Scale: Neonatal Intensive Care Unit was used. Results: The overall experience of hospitalization was classified as more stressful than the median for the sub scales. "Change in parental role" was classified as the most stressful subscale by mothers (Median (P25-P75): 4.1(32-4.7)) and fathers (Median (P25-P75): 32(2.4-4.0)). Mothers scored significantly higher in all subscales. For mothers, multiple pregnancy was associated with lower levels of stress regarding "change in parental role" (beta = -0.597; 95% CI = 1.020 to -0.174) and "overall stress" (beta = 0.603; 95% CI = 1.052 to 0.153). Being >= 30 years old was found to be a significant predictor for decreased fathers' stress. Conclusions: This study raises awareness for the need to develop sensitive instruments that take notice of gender, social support and family -centered care. The implementation of interventions focused on reducing parental stress is crucial to diminish disparities in family health.